Social Inequality: Social inequality in perceived oral health among adults in Australia - Anne E. Sanders; A. John Spencer (Elsevier, 2004)
Abstract Objective: To establish population estimates of self‐assessed tooth loss and subjective oral health and describe the social distribution of these measures among dentate adults in Australia. Methods: Self‐report data were obtained from a nationally representative sample of 3,678 adults aged 18-91 years who participated in the 1999 National Dental Telephone Interview Survey and completed a subsequent mail survey. Oral health was evaluated using (1) self‐assessed tooth loss, (2) the 14‐item Oral Health Impact Profile, and (3) a global six‐point rating of oral health. Results: While the absolute difference in tooth loss across household income levels increased at each successive age group (18-44 years, 45-64 years, 65+ years) from 0.7 teeth to 6.1 teeth, the magnitude of the difference was approximately twofold at each age group. For subjective oral health measures, the magnitude of difference across income groups was most pronounced in the 18-44 years age group. In multivariate analysis, low household income, blue‐collar occupation, and high residential area disadvantage were positively associated with social impact from oral conditions and pathological tooth loss. Speaking other than English at home (relative to English), low household income (relative to high income), and vocational relative to tertiary education were each associated with more than twice the odds of poor self‐rated oral health. Conclusions: Significant social differentials in perceived oral health exist among dentate adults. Inequalities span the socio‐economic hierarchy. Implications: In addition to improving overall levels of oral health in the adult community, goals and targets should aim to reduce social inequalities in the distribution of outcomes.